Consumption of Green Bean Extract as an Effort to Increase Hemoglobin Levels in Pregnant Women - Sari Priyanti; Agustin Dwi Syalfina; Dian Irawati; Elyana Mafticha (Universitas Widya Gama Mahakam Samarinda, 2022)
Background: Maternal mortality rate (MMR) is one of the indicators used to measure maternal health status in an area. Data in Indonesia recorded that the maternal mortality rate in 2015 was 305 per 100,000 live births, but the Sustainable Development Goals (SDG's) target is 70% per 100,000 live births in 2030. Bleeding occupies the highest percentage of maternal deaths (28%). Anemia and chronic energy deficiency (KEK) in pregnant women are the main causes of bleeding. Non-pharmacological treatment to increase hemoglobin levels by consuming foods rich in iron is green beans. Objectives: This study describes the effect of mung bean juice on hemoglobin levels. Research Metodes: This study uses a systematic review method through a literature review of 15 national journals. Results: The results of a literature search show that the consumption of green bean juice with the combination of consumption of FE tablets affects the increase in HB levels of pregnant women. However, this consumption must also be supported by good nutritional intake to accelerate the absorption and transport of iron and it is necessary to avoid drinks that affect iron absorption such as milk and caffeine. Conclusion: Green bean juice is able to significantly increase the Hb level of pregnant women with the consumption of FE tablets because the content of green beans is high in vitamin C and iron. Therefore, it is important to disseminate information to the community about the benefits and how to use mung bean juice as an effort to prevent anemia in pregnant women